2017
DOI: 10.1126/scisignal.aah6163
|View full text |Cite
|
Sign up to set email alerts
|

TCR-stimulated changes in cell surface CD46 expression generate type 1 regulatory T cells

Abstract: A lack of regulatory T cell function is a critical factor in the pathogenesis of autoimmune diseases, such as multiple sclerosis (MS). Ligation of the complement regulatory protein CD46 facilitates the differentiation of T helper 1 (T1) effector cells into interleukin-10 (IL-10)-secreting type 1 regulatory T cells (Tr1 cells), and this pathway is defective in MS patients. Cleavage of the ectodomain of CD46, which contains three N-glycosylation sites and multiple O-glycosylation sites, enables CD46 to activate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…We next assessed whether PZQ modulated cell activation by measuring the expression of the activation markers CD25, CD69 and PD‐1, and of CD46 after either 1 or 5 days of activation (Supplementary figure 2, Figure ). As expected, CD46 costimulation led to a strong decrease in CD46 surface expression due to the shedding of its ectodomain . Addition of PZQ had no significant effect on the expression of CD46 and did not significantly modulate the induction of CD69, CD25 and PD‐1.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…We next assessed whether PZQ modulated cell activation by measuring the expression of the activation markers CD25, CD69 and PD‐1, and of CD46 after either 1 or 5 days of activation (Supplementary figure 2, Figure ). As expected, CD46 costimulation led to a strong decrease in CD46 surface expression due to the shedding of its ectodomain . Addition of PZQ had no significant effect on the expression of CD46 and did not significantly modulate the induction of CD69, CD25 and PD‐1.…”
Section: Resultssupporting
confidence: 70%
“…As expected, CD46 costimulation led to a strong decrease in CD46 surface expression due to the shedding of its ectodomain. 17,18 Addition of PZQ had no significant effect on the expression of CD46 and did not significantly modulate the induction of CD69, CD25 and PD-1. PZQ has been shown to act as an adjuvant for vaccination, correlating with an increase in IL-17 and IFNc production by murine CD8 + T cells.…”
Section: Pzq Modulates Cytokine Productionmentioning
confidence: 92%
See 1 more Smart Citation
“…In terms of the regulation of CD46, it has been shown that CD46 is highly glycosylated, and that CD3 stimulation alters the O-glycosylation of CD46 in activated T-cells, resulting in decreased CD46 processing and T-cell singling, which ultimately leads to a T-reg phenotype characterized by the dominance of IL-10. Nuclear factor κB (NF-κB) has also been shown to regulate CD46 expression, where activation of NF-κB is critical for CD46 expression (65).…”
Section: The Function Of Cd46mentioning
confidence: 99%
“…Ongoing functional studies in human cells expressing/overexpressing different CD46 isoforms demonstrate clear difference in MV infection/replication and innate immune pathway activation depending on the prevalence of specific CD46 isoforms ( Haralambieva and Poland , unpublished data). Lastly, the presence/absence of STP exons (associated also with difference in the O-glycosylation) in the extracellular portion of CD46 can result in altered processing, altered CD46 shedding/cleavage by metalloproteinases, altered downregulation and cell surface expression, and profound differences in T cell function and TCR signaling [139, 140].…”
Section: Genome-wide Genetic Association Studies and Measles Vaccinatmentioning
confidence: 99%